Mariia Kultaieva is a light of thought that does not go out - Юрій Бойчук (Філософія освіти)
Words of gratitude and deep respect for Mariia Dmytrivna Kultaieva from Yurii Dmytrovych Boichuk – her colleague and rector of H.S. Skovoroda Kharkiv National Pedagogical University.